2017
DOI: 10.1088/1741-4326/aa6867
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fluid simulation of runaway electron generation in the presence of resistive kink modes

Abstract: A reduced fluid simulation is developed to study the formation of runaway current profiles in the framework of a reduced magnetohydrodynamic (MHD) model. In our simulation, three-dimensional dynamics of runaway electrons in real space is treated in terms of the equation for fluid electron density with source terms representing Dreicer and secondary generation mechanisms. The excitation of MHD instabilities, non-diffusive transport due to magnetic field fluctuation and dynamical changes of the runaway generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
6
14
0
Order By: Relevance
“…That is, when the RE current fraction is increased, the region outside the resistive layer tends towards the ideal MHD limit in which the low-resistivity analytical scaling is valid. Such a behaviour has also been observed by Matsuyama et al [167] in a similar (but not identical) case.…”
Section: Runaway Electron Fluidsupporting
confidence: 81%
See 1 more Smart Citation
“…That is, when the RE current fraction is increased, the region outside the resistive layer tends towards the ideal MHD limit in which the low-resistivity analytical scaling is valid. Such a behaviour has also been observed by Matsuyama et al [167] in a similar (but not identical) case.…”
Section: Runaway Electron Fluidsupporting
confidence: 81%
“…While various applications of the model are on their way, some studies have already been performed. Similar approaches are followed by other codes, see e.g., references [167,[285][286][287].…”
Section: Vertical Displacement Events and Halo Current Dynamicsmentioning
confidence: 99%
“…The MHD instabilities can lead to deconfinement of both runaway electrons and bulk plasma, with significant oscillations observed in ECE and interferometer signals [22]. To understand the effect of runaway electrons on MHD instabilities, efforts have been taken on both theoretical analysis and numerical simulations [23][24][25][26]. In these works, it is found that the linear growth rate of MHD instabilities is approximately the same as in a plasma without runaway electrons, but the nonlinear saturation level is different [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown in Ref. [6] that the non-linear evolution of the (1, 1) kink mode becomes insensitive to the RE advection velocity as long as it is significantly larger than the Alfvén speed.…”
Section: Introductionmentioning
confidence: 99%